Thermodynamics and Kinetics of Hydrogen Transfer Mechanism in1-[(E)-1, 3-Benzothiazol-2-Ylazo]Naphthalen-2-Ol Tautomers in Aqueous Medium/ Density Functional Theory - IBRAHIM, Asiata Omotayo; Oyebamiji, Abel Kolawole; Semire, Banjo (Iraqi Journal of Science, 2019)
Enol-Keto tautomerism in 1-[(E)-1,3-benzothiazol-2-ylazo]naphthalen-2-ol has been studied using the B3LYP functional of density functional theory (DFT) with 6-31G(d,p) basis set. Relative and absolute energies, transition state geometries (TS), dipole moments, entropies, enthalpies and Gibbs free energies, equilibrium constants (KT) and rate of tautomerization (kr) were calculated. Also, the computations of geometries and vibration frequencies for the tautomers were calculated and compared. The results of the calculations showed that the enol form is the most stable form than other isomers, this might be due to intra-hydrogen bonding. The TS1 activation energies for tautomer A ↔ B, tautomer A ↔ C and tautomer B ↔ C are 92.65, 199.56 and 225.71 kJ/mol respectively. The TS1 is lower than TS2 by 102 kJ/mol, showing that A ↔ B and B ↔ C paths are thermodynamic control and A ↔ C path is a kinetic control. The overall calculated KT ≈ 1, indicating that all tautomers present in significant proportions.